MICROBIOLOGY: PALYNOLOGY AND ITS IMPORTANCE - Cid Martínez, Marcela Alejandra (Kuxulkab', 2023)
Palynology is a scientific discipline that studies the morphological characteristics of pollen grains and fossil and current spores, also takes into account the dispersal, preservation and its application for the benefit of society. The taxonomic characters of the palynomorphs allow us to classify them, even when the plant that gave rise to them is unknown, as occurs in aerobiology, melissopalynology, forensic palynology, palinostratigraphy and archeopalynology; therefore, it is very important to know how to describe it. These microorganisms with biological indicators of the type of vegetation surrounding the study areas, which makes them valuable to know the climate in a region.
Keywords: Pollen; Pollen morphology; Sporoderm